Using the ADDIE Model of Instructional Design to Teach Chest Radiograph Interpretation. (20th June 2016) - Cheung, Lawrence
Abstract : Interpreting basic chest radiographs is an important skill for internal medicine residents to help them adequately diagnose and manage respiratory diseases. Educators need tools to ensure that they take a systematic approach when creating a curriculum to teach this, as well as other skills, knowledge, or attitudes. Using an instructional design model helps educators accomplish this task by giving them a guide they can follow to ensure that the curriculum meets the needs of the learners. Using the creation of a curriculum to teach chest radiograph interpretation as an example, this paper illustrates how educators can use the ADDIE model of instructional design to help develop their own curricula.